Identification of TEM-26 beta-lactamase responsible for a major outbreak of ceftazidime-resistant Klebsiella pneumoniae. - Urban, C (1994)
An epidemic of nosocomial ceftazidime-resistant Klebsiella pneumoniae was correlated with production of a ceftazidime-hydrolyzing enzyme with an isoelectric point of 5.6 (BMH-1). BMH-1 was encoded on a large transferable plasmid conferring multiple antibiotic resistance. The gene that encodes BMH-1 was identical to the gene that encodes the TEM-26 extended-spectrum beta-lactamase.